Temporal Trends in Internal vs. External Referrals for TAVR in a Large Academic Center: Patients Characteristics and Outcomes - Aurelie Merlo; Audrey Khoury; Mohsin Shah; Tabitha Linville; John Ikonomidis; Matthew Cavender; John Vavalle; Thomas Caranasos (Journal of Interventional Cardiology)
Background. Since transcatheter aortic valve replacement (TAVR) first became approved for inoperable patients followed by high, intermediate-, and low-risk patients, referrals to TAVR centers have rapidly increased. The purpose of this study was to investigate referral patterns to a large academic TAVR center in the state of North Carolina and evaluate differences between externally and internally referred patients. Methods. Data for all patients who underwent TAVR at our institution between November 2014 and March 2020 were pulled from the Transcatheter Valve Therapy Registry. The electronic medical record was used to determine the referral source. The descriptive statistical analysis was performed using Excel (Microsoft, Redmond, Washington). Results. 491 patients underwent TAVR at our institution between November 2014 and March 2020. Half of the patients were referred by a cardiologist within the same health system (N = 250, 50.9%). Other referral sources included a cardiologist external to the health system (N = 210, N = 42.8%) and a surgeon or proceduralist (such as urologist, surgeon, or gastroenterologist) during the workup for another procedure (N = 26, 5.3%). Over time, there was a trend toward an increasing proportion of patients referred by a cardiologist external to our system, but this trend did not reach statistical significance (20.0% in 2014, 29.2% in 2015, 30.7% in 2016, 53.0% in 2017, 36% in 2018, 48.4% in 2019, and 56.8% in 2020, p=0.06 using the Mann–Kendall trend test). Externally referred patients were less likely to have private insurance and were more likely to have a reduced ejection fraction and had a higher mean gradient across the valve. Postprocedure, externally referred patients were more likely to have the procedure under moderate sedation and less likely to be discharged home. Conclusions. This study presents the referral pattern to a large TAVR center in North Carolina. Over time, there was an increase in external referrals suggesting that TAVR is increasingly adopted as an important component of the management of aortic valve stenosis. Internally and externally referred patients have differences in baseline demographic and clinical characteristics which may have an impact on clinical outcomes.